Value and Values Economics and Justice in an Age of Global Interdependence - Ames, Roger T.; Ames, Roger T.; Behuniak, James Jr; Bein, Steve; Bhushan, Nalini; Bilimoria, Purushottama; Burik, Steven; Chatterjee, Amita; Cheng, Baoyan; Davis, Gordon; Di, Xu; Garfield, Jay L.; et al. (University of Hawaii Press, 2015)
The most pressing issues of the twenty-first century-climate change and persistent hunger in a world of food surpluses, to name only two-are not problems that can be solved from within individual disciplines, nation-states, or cultural perspectives. They are predicaments that can only be resolved by generating sustained and globally robust coordination across value systems. The scale of the problems and necessity for coordinated global solutions signal a world historical transit as momentous as the Industrial Revolution: a transition from the predominance of technical knowledge to that of ethical deliberation.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 29. Jul 2021)
Keywords: PHILOSOPHY / Ethics & Moral Philosophy; Economics -- Moral and ethical aspects -- Congresses